Genes Found Essential in Other Mycoplasmas Are Dispensable in Mycoplasma bovis - Sharma, Shukriti (Public Library of Science, 2014)

(untitled)
Mycoplasmas are regarded to be useful models for studying the minimum genetic complement required for independent survival of an organism. Mycoplasma bovis is a globally distributed pathogen causing pneumonia, mastitis, arthritis, otitis media and reproductive tract disease, and genome sequences of three strains, the type strain PG45 and two strains isolated in China, have been published. In this study, several Tn4001 based transposon constructs were generated and used to create a M. bovis PG45 insertional mutant library. Direct genome sequencing of 319 independent insertions detected disruptions in 129 genes in M. bovis, 48 of which had homologues in Mycoplasma mycoides subspecies mycoides SC and 99 of which had homologues in Mycoplasma agalactiae. Sixteen genes found to be essential in previous studies on other mycoplasma species were found to be dispensable. Five of these genes have previously been predicted to be part of the core set of 153 essential genes in mycoplasmas. Thus this study has extended the list of non-essential genes of mycoplasmas from that previously generated by studies in other species.